Boy and Girl Scouts. - Unknown:::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a Boy Scout drum and bugle corps at Santa Anita, California Assembly Center led by Girl Scout majorettes.